Internet Marketing By Implementing Enterprise Resource Planning (ERP) At The Mukomuko Milk Center Using Php Programming Language And Mysql Database - Radius Prawiro (Sustainability (STPP) Theory, Practice and Policy, 2022)
This study describes about design of internet marketing by implementing ERP which is supported by a MySQL database and the PHP programming language. From the research conducted at Sentra Susus Sapi Mukomuko, it can be concluded that the old system used was ineffective because the process take a long time and space, thus making the performance of employees less efficient. After conducting research at Senstra Susu Sapi Mukomuko the researcher using interview methods and other methods, it can be concluded that the information system used is still not optimal. Therefore, the output design, input design, file design and program flow of the new system are carried out. The results of the analysis are applied to an ERP program. The new information system designed is expected to improve the quality of information and performance in the future.